Advanced materials science and engineering of carbon - Inagaki, Michio; Kang, Feiyu; Toyoda, Masahiro; Konno, Hidetaka (Butterworth-Heinemann, 2014)
Covers the most recent advances in carbon materials, including new techniques and processes, carbon materials synthesis, and up-to-date descriptions of current carbon-based materials, trends and applications.
Includes index.
Keywords: Materials.; Carbon composites.; elektronické knihy; electronic books